Saprotrophic Wood Decay Ability and Plant Cell Wall Degrading Enzyme System of the White Rot Fungus Crucibulum laeve: Secretome, Metabolome and Genome Investigations - Alexander V. Shabaev; Olga S. Savinova; Konstantin V. Moiseenko; Olga A. Glazunova; Tatyana V. Fedorova (Journal of Fungi)
The basidiomycete Crucibulum laeve strain LE-BIN1700 (Agaricales, Nidulariaceae) is able to grow on agar media supplemented with individual components of lignocellulose such as lignin, cellulose, xylan, xyloglucan, arabinoxylan, starch and pectin, and also to effectively destroy and digest birch, alder and pine sawdust. C. laeve produces a unique repertoire of proteins for the saccharification of the plant biomass, including predominantly oxidative enzymes such as laccases (family AA1_1 CAZymes), GMC oxidoreductases (family AA3_2 CAZymes), FAD-oligosaccharide oxidase (family AA7 CAZymes) and lytic polysaccharide monooxygenases (family LPMO X325), as well as accompanying acetyl esterases and loosenine-like expansins. Metabolomic analysis revealed that, specifically, monosaccharides and carboxylic acids were the key low molecular metabolites in the C. laeve culture liquids in the experimental conditions. The proportion of monosaccharides and polyols in the total pool of identified compounds increased on the sawdust-containing media. Multiple copies of the family AA1_1, AA3_2, AA7 and LPMOs CAZyme genes, as well as eight genes encoding proteins of the YvrE superfamily (COG3386), which includes sugar lactone lactonases, were predicted in the C. laeve genome. According to metabolic pathway analysis, the litter saprotroph C. laeve can catabolize D-gluconic and D-galacturonic acids, and possibly other aldonic acids, which seems to confer certain ecological advantages.